2006
DOI: 10.1007/s11071-006-9123-z
|View full text |Cite
|
Sign up to set email alerts
|

The bouncing motion appearing in a robotic system with unilateral constraint

Abstract: The hopping or bouncing motion can be observed when robotic manipulators are sliding on a rough surface. Making clear the reason of generating such phenomenon is important for the control and dynamical analysis for mechanical systems. In particular, such phenomenon may be related to the problem of Painlevé paradox. By using LCP theory, a general criterion for identifying the bouncing motion appearing in a planar multibody system subject to single unilateral constraint is established, and found its application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Recent studies have indicated that the Painlevé paradox may be a common phenomenon and could be found in a variety of different applications such as robotic manipulation, legged locomotion, and vehicle braking systems [15,26,27,28]. Especially, according to our recent work for a robotic system that comes into contact with a moving belt [28], the Painlevé paradox will appear even though the coefficient of friction takes a very small value.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Recent studies have indicated that the Painlevé paradox may be a common phenomenon and could be found in a variety of different applications such as robotic manipulation, legged locomotion, and vehicle braking systems [15,26,27,28]. Especially, according to our recent work for a robotic system that comes into contact with a moving belt [28], the Painlevé paradox will appear even though the coefficient of friction takes a very small value.…”
Section: Introductionmentioning
confidence: 94%
“…An experimental setup corresponding to the analytical model presented in our prior work [28] is developed, in which a two-link robotic system comes into contact with a moving rail. The experimental results clearly show that a tangential impact does exist at the contact point and takes a peculiar property well coinciding with the maximum dissipation principle stated in [11] by Moreau; the relative tangential velocity of the contact point must immediately approach zero once a Painlevé paradox occurs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations